PENGARUH PENGGUNAAN VIDEO ANIMASI TERHADAP HASIL BELAJAR SISWA PADA MATERI SIKLUS AIR di KELAS V SDN 1 PATARUMAN - Ratna Sariningsih, Ida; Akhmad Nugraha; Pidi Mohamad Setiadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was conducted to determine the effect of using animated video media on students' learning outcomes in science subjects at SDN 1 Pataruman. The background of this study is the low learning outcomes of students in science subjects, particularly the water cycle material, which is suspected to be due to the lack of engaging and interactive learning media. This study aims to improve students' learning outcomes by using animated video media, which is expected to make learning more interesting and easier to understand. The research method used is quasi-experimental with a pre-test and post-test only control group design. The research subjects consisted of 32 fifth-grade students divided into two groups: an experimental class using animated video media and a control class using conventional media. Data were collected through multiple-choice tests conducted before and after the treatment. The results showed a significant improvement in the learning outcomes of students in the experimental class compared to the control class. The average pre-test score of the experimental class was 4.26 and increased to 8 in the post-test. Meanwhile, the average pre-test score of the control class was 4.52 and increased to 6.47 in the post-test. The N-Gain calculation showed that the experimental class achieved an average N-Gain of 66.72% (quite effective), while the control class achieved an average N-Gain of 34.48% (ineffective). Statistical analysis using the t-test indicated that the difference in learning outcomes between the two groups was significant with a significance value of 0.004 at the 0.05 significance level. Thus, the use of animated video media has proven effective in improving students' learning outcomes in science subjects.